Craniofacial Morphology in Patients With Opitz G/BBB Syndrome - Dalben, Gisele da Silva; Garib, Daniela Gamba; Pinto, Rayane de Oliveira [UNESP]; Richieri-Costa, Antonio; Taveira, Luís Antônio de Assis (SAGE Publications, 2019)
Objective: To compare the cephalometric characteristics of patients with and without Opitz G/BBB syndrome type I. Design: Cross-sectional, case–control study. Setting: Tertiary cleft center in Brazil. Participants: Eighteen individuals with Opitz G/BBB syndrome with complete bilateral cleft lip and palate (BCLP), compared to 18 individuals with nonsyndromic complete cleft lip and palate and 18 individuals without malformations, matched for gender and age. Interventions: Pretreatment lateral cephalograms of all patients were manually traced and digitized for achievement of linear and angular measurements. Main Outcome Measures: Analysis of variance or Kruskal-Wallis followed by Tukey tests were used for intergroup comparisons at a significance level of P <.05. Results: Individuals with Opitz G/BBB syndrome exhibited alterations in SNGn, P-Co, and N’-Pr/Po-Or that were not attributable to BCLP. Co-Go, Sella-Nasion-Supramentale, ANB (maxillo-mandibular relationship), and anterior nasal spine-posterior nasal spine (ANS-PNS)/U1A-U1T were significantly different in both G/BBB and BCLP groups compared to control, but not different between G/BBB and BCLP groups. Anterior nasal spine-posterior nasal spine/Go-Gn, ANS-PNS, V-Upper pharyngeal wall, and U-lower pharyngeal wall were different in nonsyndromic BLCP compared to nonsyndromic controls and Opitz G/BBB group. Conclusion: Patients with Opitz G/BBB syndrome exhibited some unique cephalometric alterations compared to patients with nonsyndromic complete BCLP and controls.
Keywords: cephalometrics; craniofacial morphology; Opitz syndrome